Participatory worlds: models of collaborative textual production beyond the entertainment industry - Blázquez, José M. (University of Malta, 2016)
Throughout history, participation has been a term closely related to transgression and the democratisation and the balance of the inequalities in society. Participation has continued being a major concept in the digital age where 'participatory culture', a culture where audiences get the framework, knowledge and tools to take part in the creation and production of content, has becoming more popular and visible than ever before. Co-creation practices between producers and consumers (also known as value co-creation or co-creation of value) has been seen for many academics, gurus and organizations as a way to generate industrial innovation in the near future. Software development and testing, ‘modding’, knowledge exchange and participatory journalism are areas where user participation has been applied successfully. However, there are other disciplines where co-creation practices have seen very little improvement within the industry. This is the case of narrative contributions to story-worlds. Entertainment industries, IP owners of the most popular franchises, generally keep a strict control over their fictional worlds and user participation may only be considered as a part of a marketing strategy, market research and customer feedback. Even when channels for participation exist (for example, in the form of a contest), narrative contributions created by fans are merely treated as fan-fiction.